A Game of Code: Challenges of Cyberspace as a Domain of Warfare - Rosana Nyabuto, Christopher (Strathmore Law Review, 2018)
The military capabilities that the world witnesses in modern day armed conflicts are a sort of science fiction brought to life. Most of the techniques in cyber warfare were never thought possible, let alone anticipated in times past especially during the framing of key International Humanitarian Law (IHL) instruments. This paper analyses the challenges that cyber warfare poses to state responsibility. The analysis also discusses how the anonymity of parties in cyber warfare presents challenges to the application of existing law. The rationale for this study is the fact that cyberspace as a domain of warfare is still in its early days despite the many ambiguities and puzzles it has sparked in various circles of discussion. The study relies on literature reviews and case studies to make its salient points. Ultimately, the study argues that cyber warfare is subject to IHL; however, it breeds new possibilities that may require greater adherence to consistent legal review of weapons and greater willingness of the international community to apply IHL to this domain of warfare.